Acellular dermal tissue study: an ultrastructural evaluation of human and porcine derived tissues in a rat model - Hoyama, E.; Schellini, Silvana Artioli [UNESP]; Gregório, E. A.; Rossa, R. (My University, 2004)
The purpose of this study was to evaluate the host response of a human and a porcine derived acellular dermal tissue (ADT) implanted in the subcutaneous tissue of a rat model. Two subcutaneous pockets were surgically created along the dorsal midline of 25 rats (5 rats/group). The human ADT was placed superiorly and the porcine ADT, inferiorly. The animals were sacrificed at 07, 15, 30, 60 and 180 postoperative days (PO) and the ADTs and surrounding soft tissues were assessed for ultrastructural evaluation by transmission electron microscopy. The ultrastructural findings were similar in both materials. Normal collagen and elastic fibers bundles were observed during all experimental moments, as well as macrophages presenting cytoplasmic enlargements digesting cellular portions after 15 PO. From 30 until 180 PO, vacuolar structures filled with an amorphous, electron-transparent substance, were present inside and outside the fibroblasts. Both human and porcine ADT showed similar pattern of ultrastructural response when implanted in the subcutaneous tissue of rats. The porcine ADT appears as a good alternative to be used as a biomaterial.
Keywords: Acellular dermal tissue; Biomaterial; Experimental study; Ultrastructure; collagen; animal experiment; animal tissue; controlled study; cytoplasm; dermis; elastic fiber; fibroblast; macrophage; male; nonhuman; rat; soft tissue; subcutaneous tissue; transmission electron microscopy; ultrastructure; Animals; Collagen; Eosinophils; Fibroblasts; Humans; Macrophages; Male; Microscopy, Electron, Transmission; Models, Animal; Rats; Skin; Skin Transplantation; Subcutaneous Tissue; Swine; Vacuoles